INVESTIGATING THE COST EFFECTIVENESS OF BIODIESEL DISTRIBUTION IN INDONESIA - Herbert Wibert Victor Hasudungan; Elis Heviati; Sulthon Sjahril Sabaruddin; Sigit Hargiyanto (Economic Review)
The implementation of biodiesel in Indonesia has been regarded as one of the main strategies to improve country’s energy security equally and equitably. However, as the largest archipelago country in the world, the activity in distributing their biodiesel production bears a key problem. The complexity of delivering biodiesel from the supply point to the blending terminal of gasoil might result in cost inefficiency, which in turn will escalate the government funding of biodiesel incentives. This paper aims to both evaluate and formulate the Indonesian biodiesel transportation costs in all routes using either trucking or shipping mode. Based on primary data and information obtained from experts, we found that the most dominant factors that affect the shipping distribution cost are the size of the ship and its activities (such as voyage, ballast, loading, discharge, waiting, and buffer), whilst for the trucking mode, the dominant factors are both its corresponding operational costs and investment costs. Given that fuel prices fluctuate periodically, we also argue that the cost differences between the regulated and formulated reference may arise due to i) the data inaccuracy of the diesel fuel consumption and ii) specific terms outlined in the agreement between the corresponding transporters and suppliers.